Mars entry guidance based on an adaptive reference drag profile - Liang, Zixuan; Duan, Guangfei; Ren, Zhang (Advances in space research, 2017)
The conventional Mars entry tracks a fixed reference drag profile (FRDP). To improve the landing precision, a novel guidance approach that utilizes an adaptive reference drag profile (ARDP) is presented. The entry flight is divided into two phases. For each phase, a family of drag profiles corresponding to various trajectory lengths is planned. Two update windows are investigated for the reference drag profile. At each window, the ARDP is selected online from the profile database according to the actual range-to-go. The tracking law for the selected drag profile is designed based on the feedback linearization. Guidance approaches using the ARDP and the FRDP are then tested and compared. Simulation results demonstrate that the proposed ARDP approach achieves much higher guidance precision than the conventional FRDP approach.